2011
DOI: 10.1136/ard.2010.140178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cane use on pain, function, general health and energy expenditure during gait in patients with knee osteoarthritis: a randomised controlled trial

Abstract: Objective To assess the impact of daily cane use during gait in relation to pain, function, general health and energy expenditure among patients with knee osteoarthritis. Method Sixty-four patients were randomly assigned to an experimental group (EG) or control group (CG). The EG used a cane every day for 2 months, whereas the CG did not use a cane in this period. The fi rst outcome was pain and the second were function (Lequesne and WOMAC), general health (SF-36) and energy expenditure (gas analysis during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 37 publications
0
49
1
6
Order By: Relevance
“…22 Contralateral cane use can also effectively diminish pain and improve function and some aspects of quality of life in patients with knee OA. 103 Recent randomized clinical trials of patients with knee OA demonstrated significantly diminished pain and improved physical function after 2 months of daily cane use. 103,135 For optimal efficacy, patients with knee OA should be instructed to use a cane on the contralateral side and as far laterally as possible to optimize reductions in knee loads.…”
Section: Contralateral Cane Usementioning
confidence: 99%
See 2 more Smart Citations
“…22 Contralateral cane use can also effectively diminish pain and improve function and some aspects of quality of life in patients with knee OA. 103 Recent randomized clinical trials of patients with knee OA demonstrated significantly diminished pain and improved physical function after 2 months of daily cane use. 103,135 For optimal efficacy, patients with knee OA should be instructed to use a cane on the contralateral side and as far laterally as possible to optimize reductions in knee loads.…”
Section: Contralateral Cane Usementioning
confidence: 99%
“…103 Recent randomized clinical trials of patients with knee OA demonstrated significantly diminished pain and improved physical function after 2 months of daily cane use. 103,135 For optimal efficacy, patients with knee OA should be instructed to use a cane on the contralateral side and as far laterally as possible to optimize reductions in knee loads. Placing the cane at a longer lateral distance can create neutralizing knee abduction moments to further counteract and decrease KAM during gait.…”
Section: Contralateral Cane Usementioning
confidence: 99%
See 1 more Smart Citation
“…6 Mobility aids such as a stick (used in the opposite hand), knee braces and foot orthoses can also diminish pain and improve function. [7][8][9] Obesity is the single most important modifiable risk factor. 2,10 A meta-analysis found that a 5% decrease in weight within a 20-week period is beneficial for knee osteoarthritis.…”
mentioning
confidence: 99%
“…A study which evaluated the effect of using walking sticks revealed that for patients who used them for two months, a small but significant amount of improvement occurred in their pain and function (effect sizes 0.18, 95% CI -0.42-0.87 and 0,13, 95% CI -0.11-0.42, respectively) (LOE Ib). [27] If involvement is unilateral, sticks or crutches should be used contralaterally. In case of bilateral involvement, simple walkers or walkers with rollers should be the preference.…”
mentioning
confidence: 99%